2016
DOI: 10.4238/gmr15048874
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal number of markers and individuals in a training population necessary for maximum prediction accuracy in F<sub>2</sub> populations by using genomic selection models

Abstract: ABSTRACT. Genomic selection is a useful technique to assist breeders in selecting the best genotypes accurately. Phenotypic selection in the F 2 generation presents with low accuracy as each genotype is represented by one individual; thus, genomic selection can increase selection accuracy at this stage of the breeding program. This study aimed to establish the optimal number of individuals required to compose the training population and to establish the amount of markers necessary to obtain the maximum accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the present study, prediction accuracies for CBSD3s and CBSDRs were 8% and 18% higher for high-density (WGS-imputed) markers than low-density (GBS) markers from single kernel G-BLUP model for the optimized training population of size of 200 clones (Table S11). Several studies have demonstrated increased prediction accuracies as a function of increase marker density (Peixoto et al , 2016; Wang et al , 2017). In a recent study, using NaCRRI training population, prediction for CBSD-related traits, in a single kernel G-BLUP model was not improved by whole-genome imputation (Lozano et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, prediction accuracies for CBSD3s and CBSDRs were 8% and 18% higher for high-density (WGS-imputed) markers than low-density (GBS) markers from single kernel G-BLUP model for the optimized training population of size of 200 clones (Table S11). Several studies have demonstrated increased prediction accuracies as a function of increase marker density (Peixoto et al , 2016; Wang et al , 2017). In a recent study, using NaCRRI training population, prediction for CBSD-related traits, in a single kernel G-BLUP model was not improved by whole-genome imputation (Lozano et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Each linkage group was simulated with 100 cM, comprising 100 codominant molecular markers, spaced equidistantly (1 cM), totaling 1000 markers. The number of markers used in the simulation is considered adequate for the study purpose and is similar with other simulations studies (Oliveira et al 2021;Peixoto et al 2016, Sant' Anna et al 2019.…”
Section: Simulation Of Phenotypic and Genotypic Datamentioning
confidence: 79%
“…Bhering et al (2015) and Spindel et al (2015) showed that a small number of markers can be used for high precision genomic selection for many traits. Peixoto et al (2016), in a study with simulated data, concluded that a genomic selection model that uses 300-800 markers is sufficient to capture all the genetic variance, and to decrease the residual variance, to obtain the maximum prediction precision of an F 2 population.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not do it because we had problems with the DNA extraction, and just a few plants could be evaluated. When we estimated these parameters using all plants in the experiment this problem was solved as showed by Junqueira et al [ 25 ] and Peixoto et al [ 41 ].…”
Section: Discussionmentioning
confidence: 99%